Economic optimisation of European supply chains for CO2 capture, transport and sequestration, including societal risk analysis and risk mitigation measures. (1st August 2018) - d'Amore, Federico; Mocellin, Paolo; Vianello, Chiara; Maschio, Giuseppe; Bezzo, Fabrizio
Graphical abstract: Highlights: A model for optimising the European carbon capture and sequestration (CCS) is proposed. Societal risk analysis is incorporated within the CCS model. Risk mitigation measures are included as options for local risk reduction. Scenarios assessing different risk definitions and policies are implemented. Societal risk does not affect CCS costs significantly, but limits the sequestration potential. Abstract: European large stationary sources are currently emitting more than 1.4 Gt of CO2 every year. A significant decrease in greenhouse gases emissions cannot be achieved without carbon capture and sequestration (CCS) technologies. However, although being practiced for over 30 years, CO2 transportation is intrinsically characterised by the risk of leakage. This study proposes to assess and tackle this issue within the CCS design problem, by proposing a spatially explicit mixed integer linear programming approach for the economic optimisation of a European supply chain for carbon capture, transport and geological storage, where societal risk assessment is formally incorporated within the modelling framework. Post-combustion, oxy-fuel combustion and pre-combustion are considered as technological options for CO2 capture, whereas both pipelines (inshore and offshore) and ships are taken into account as transport means. Both inland-inshore and offshore injection options are available for carbon geological sequestration. Risk mitigation measures are considered in the design of the transport network. The overall supply chain is economically optimised for different minimum carbon reduction scenarios. Results demonstrate that accounting for societal risk may impact the overall carbon sequestration capacity, and that the proposed approach may represent a valuable tool to support policy makers in their strategic decisions.